Approach to the Physical Ability Balance in the Elderly - Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo; Fernando Jesús del Sol Santiago (Revista Finlay)
The accelerated aging process of the population and the ways of treating physical capacities in this population set guidelines for this review which was aimed at valuing the ways of approaching the coordinative physical capacity balance in the elderly. An electronic search was realized in the following data base: Scopus, EMBASE/Excerpta Médica, Latindex, IBECS, MEDLINE, PudMed, ScienceDirect y SciELO. The descriptors analyzed were deterioration of the capacity balance, capacity balance, elder adults, balance injured capacity. The main selected studies analyzed the results through statistic reliable criteria. A total of 61 studies were selected and 9 complied the criteria of inclusion. The assessment allowed exposing the different ways of approaching this capacity from the new perspectives of evaluation and treatment y changes are proposed in the strategies of intervention and evaluation to modify and restore the deterioration produced in the aging process.